2020
DOI: 10.1021/acs.inorgchem.0c00694
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofN,NCoordination and RuIIHalide Bond in Enhancing Selective Toxicity of a Tyramine-Based RuII(p-Cymene) Complex

Abstract: Ruthenium compounds are promising anticancer candidates owing to their lower side-effects and encouraging activities against resistant tumors. Half-sandwich piano-stool type Ru II compounds of general formula [(L)Ru II (η 6 -arene)(X)] + (L = chelating bidentate ligand, X = halide) have exhibited significant therapeutic potential against cisplatin-resistant tumor cell lines. In Ru II (p-cymene) based complexes, the change of the halide leaving group has led to several interesting features, viz., hydrolytic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 89 publications
2
25
0
Order By: Relevance
“…The tripeptide glutathione (γ‐ l ‐Glu‐ l ‐Cys‐Gly; GSH) is an abundant (m m ) intracellular thiol that is known to cause the detoxification of heavier transition‐metal ions, including several platinum and ruthenium anticancer compounds, which have an affinity towards sulfur [47] . However, Wang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tripeptide glutathione (γ‐ l ‐Glu‐ l ‐Cys‐Gly; GSH) is an abundant (m m ) intracellular thiol that is known to cause the detoxification of heavier transition‐metal ions, including several platinum and ruthenium anticancer compounds, which have an affinity towards sulfur [47] . However, Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…The tripeptide glutathione (g-l-Glu-l-Cys-Gly; GSH) is an abundant (mm)i ntracellular thiol that is known to cause the detoxification of heaviert ransition-metal ions, including several platinum and ruthenium anticancer compounds,w hich have an affinity towards sulfur. [47] However, Wang et al reported ap ossibly conflicting role of GSH in the mechanism of action of Ru IIarene complexes,w hich may contribute to the lack of cross-resistancef or platinum-based therapeutics. [48,49] The interaction of complexes C5 and C13 with GSH was studied by 1 HNMR spectroscopy;t he spectra were recorded over ap eriod of 24 h, after the addition of ak nown amount of the respective complex in [D 6 ]DMSO to a1 0-folde xcessc oncentration of GSH in D 2 O(see Figure S80 in the Supporting Information).T he experimental conditions were the same as used in the solution stability studies.…”
Section: Solution Behavior Of C5 and C13mentioning
confidence: 99%
“…In this regard, a very high number of new organometallic ruthenium agents have been reported as potential candidates for clinical translation. Many examples of the screening of mono-, di-, and poly-nuclear ruthenium compounds with biologically inactive and active auxiliar ligands to give chiral and achiral complexes have been reported by advanced biological methods to understand their mechanism of action [27][28][29][30][31][32][33][34]. In this context, successful ruthenium complexes have been reported for the treatment of breast cancer [35].…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53] Effect of halide interchange showed remarkable differences in the mechanism of action in certain iminopyridine and azopyridine based ligands and their corresponding Ru II (η 6 -p-cymene) complexes. [50,54] The iodido coordinated Ru II complexes show more kinetic inertness and better activity against various forms of cancer including A2780 (ovarian), MCF-7 (breast), HCT116 (colon) and MIA PaCa-2 (pancreatic) cell lines. Certain iodido coordinated Ru II complexes show high potency towards cisplatin-resistant ovarian cancer (A2780cisR), oxaliplatin-resistant colon cancer (HCT116Ox) and p53-null colon cancer (HCT116p53-/À ) cells suggesting p53-independent cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[49] There are examples where the Ru II -iodido complexes are internalized more in cancer cells. [54][55] Among the various forms of cancer, breast cancer is the second most common cancer in the world and ranks fifth for its fatality. [56] Triple-negative breast cancer (TNBC) is a highly aggressive and metastatic phenotype of breast cancer with a poor prognosis and high relapse rate due to the absence of three major targeting receptors estrogen, progesterone and HER2.…”
Section: Introductionmentioning
confidence: 99%